Changes to the littered cigarette pack environment in New York City between 2011 and 2015. Issue 3 (30th May 2019) - Farley, Shannon M; Jasek, John P; Sacks, Rachel; Schroth, Kevin; Davis, Kevin
Abstract : Introduction: Imposing policies that increase tobacco prices is a key strategy for reducing smoking prevalence, although it may result in more cigarette trafficking. In 2013, New York City (NYC) passed the Sensible Tobacco Enforcement (STE) law requiring cigarettes be sold for a minimum price of $10.50 per pack. To evaluate whether cigarette price increases changed patterns of behaviour related to cigarette tax evasion, we examined littered pack study data from 2011 and 2015. Methods: Littered cigarette packs were collected from a random sample of NYC census tracts in 2011 and 2015. The proportions of cigarette packs with proper local, known non-local, foreign or unknown, and no tax stamp were calculated. Changes in volume, source and consumption of domestically trafficked cigarettes over time were estimated. Results: In 2011, 255 packs with cellophane were collected; in 2015, 226 packs with cellophane were collected. Packs without proper local stamp increased from 60.7% in 2011 to 76.3% in 2015 (p<0.05) and those with foreign or unknown stamp increased from 11.6% in 2011 to 31.4% in 2015 (p<0.05). The percentage of domestically sourced packs attributed to domestic trafficking increased significantly from a range of 47.9% to 52.8% in 2011 to a range of 59.4% to 63.2% in 2015. Conclusion: While the trafficking rate among domestically sourced cigarettes increased between 2011 and 2015 (before and after the STE minimum price floor on cigarette packs was in place), there was a decline in total consumption of domestically trafficked cigarettes due to a significant increase in consumption of foreign-sourced cigarettes. Jurisdictions considering price measures should bolster monitoring and enforcement efforts to maximise public health impact. Given the interstate nature of cigarette trafficking in the USA, Federal intervention would be optimal.